Avaliação externa da alfabetização : o PAEBES-ALFA no Espírito Santo - Côco, Dilza (2014)
The work integrates studies developed by the Education and Languages (verbal) research line, of the Post-Graduation Program in Education from the Espírito Santo State Federal University. It is about a qualitative research, structured in the form of a study case that uses the external evaluation in literacy as main theme. It focus the Espírito Santo Program of Basic Education Evaluation – Literacy (Paebes-Alfa), from documental sources and actions of external evaluation of the Portuguese Language area occurred in the classrooms of first and second grades of Elementary School belonging to the Municipal Education in the district of Serra/ES. The study aims at understanding the senses produced for this evaluation in the context of the literacy practices. The research starts from the premise that the external evaluations have been producing the idea to improve the education quality through emptying the school curriculums, that is, through the denial to the popular class to access essential knowledge in order to obtain a good citizen formation. For collating such thesis, analysis based on theoretical contributions of the language discursive perspective, are developed, proposed by Bakhtin circle and on the concepts of the Political Sociology field, and defended by Stephen J. Ball. These analyzes are organized in two discussion axles. The first one, the program document discursive contents are explored, published in the year 2012, period when the research field was performed, addressed to the professionals linked to the schools, as two test application manuals, three magazines directed to Managers and other three magazines, which the privileged social audience are the Teachers. In the second discussion axle, texts (oral and written) produced by the individuals involved with the literacy work held at schools, as School Principals, Pedagogues, Teachers and children experiencing the events of the Paebes-Alfa evaluation, are analyzed. The analyzes developed through these two discussion axles conclude that Paebes-Alfa links the conceptions restricted to the evaluation, the language and literacy, especially by privileging the knowledge of the linguistic dimension of the mother tongue appropriation process, disregarding the aspects of the language discursive dimension